Compatibility Measurement in Social Network Analysis: Literature Review - Tanty Yanuar Widiyanti (Journal of INISTA, 2020)
Social network has become one of method to discover the position of each agent. Social Network Analysis can visualize the connections nodes who is people in social network. in some purpose, SNA becoming one motivation to understand the detailed characteristics that can be used to enhance the learning environment. Another motivation is to understand the interaction pattern and identity people for real-time. This paper is to compare and find compatibility measurement from across study in SNA. Therefore, the study found that centrality is the most measurement to use in SNA.